2022
DOI: 10.1139/cjps-2022-0036
|View full text |Cite
|
Sign up to set email alerts
|

Fall-applied residual herbicides improve broadleaf weed management in ultra-early wheat (Triticum aestivum L.) production systems on the northern Great Plains

Abstract: Ultra-early spring wheat ( Triticum aestivum L.) planting systems based on soil temperature on the northern Great Plains have lower overall variability in grain yield, and can increase grain yield relative to current calendar date-based spring wheat planting systems used in the region. However, ultra-early planting when soils are cold (2 °C), and resulting early crop emergence, precludes most foliar pre-seeding weed control options. Field trials were conducted at three sites in western Canada from 2017 to 2019… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Slafer et al (2023) reported that grain yield was a function of the length of the wheat critical growth period and the growing conditions during that period. In ultra-early planting systems, the critical developmental period of wheat shifts to earlier in the growing season, occurs under cooler temperatures, and potentially lasts longer than when planting occurs later in the season (Collier et al, 2020(Collier et al, , 2021Collier, Spaner, Hall, et al, 2022). By shifting these sensitive growth stages earlier in the growing season, ultra-early planting has the potential to increase grain yield by optimizing wheat phenology within predominant environmental conditions on the northern Great Plains.…”
Section: 4mentioning
confidence: 99%
See 2 more Smart Citations
“…Slafer et al (2023) reported that grain yield was a function of the length of the wheat critical growth period and the growing conditions during that period. In ultra-early planting systems, the critical developmental period of wheat shifts to earlier in the growing season, occurs under cooler temperatures, and potentially lasts longer than when planting occurs later in the season (Collier et al, 2020(Collier et al, , 2021Collier, Spaner, Hall, et al, 2022). By shifting these sensitive growth stages earlier in the growing season, ultra-early planting has the potential to increase grain yield by optimizing wheat phenology within predominant environmental conditions on the northern Great Plains.…”
Section: 4mentioning
confidence: 99%
“…Ultra-early planting when soils are cold (≤2˚C), and resulting early crop emergence, precludes most foliar pre-seeding weed control options. Collier, Spaner, Hall, et al (2022) conducted field experiments at three sites in western Canada from 2017 to 2019 to evaluate the crop safety, broadleaf weed efficacy, and growing system stability resulting from the inclusion of fall applications of soil-applied residual herbicides prior to planting wheat ultra-early the following spring. Flumioxazin (protoporphyrinogen oxidase inhibitor; Weed Science Society of America [WSSA] group 14) and pyroxasulfone (very-long-chain fatty acid synthesis inhibitor; WSSA group 15) were applied alone and in combination at multiple rates in the late fall prior to ground freeze.…”
Section: System Responses To Ultra-early-planted Wheatmentioning
confidence: 99%
See 1 more Smart Citation
“…The drill was first used in conjunction with a newly conceptualized seeding system for wheat--"ultra-early wheat", and was first detailed in interim and final reports for that project (Beres et al 2018). It was further described in the subsequent studies and publications of ultra-early wheat seeding systems (Collier et al 2020b(Collier et al , 2021(Collier et al , 2022a(Collier et al , 2022b.…”
mentioning
confidence: 99%